Process optimization and anti-oxidative activity of peanut meal Maillard reaction products. (November 2018) - Qinzhu, Zeng; Yan-ling, Cui; Dong-xiao, Su; Tian, Bin; Yang, Yuan; Shan, He
Abstract: By applying bacterial and enzymatic processes, peanut meal, the by-product of peanut oil meal production, was used to create the value-added product - peanut meal hydrolysates in this study. The flavor of peanut meal hydrolysates was enhanced through the Maillard reaction. The optimized processing conditions for producing peanut meal Maillard reaction products (MRPs) with flavor enhancement were determined as a processing temperature of 115 °C, a processing time of 35 min, an initial pH of 7, and an initial xylose concentration of 1% (w/v). The anti-oxidative activities of peanut meal hydrolysates and peanut meal hydrolysate MRPs were compared via the methods of DPPH radical scavenging activity, hydroxyl radical scavenging radical activity, and lipid peroxidation inhabitation. All these 3 methods confirmed the enhanced anti-oxidative activity of peanut meal hydrolysates after the Maillard reaction. Gas chromatography-mass spectrometry (GC-MS) analysis determined that the reason for this enhancement was due to an increased percentage of anti-oxidative compounds, mainly phenolic compounds (from 70.61% to 92.39%), along with other compounds such as Propylthiouracil, hexahydropyrrolo [1, 2-a]pyrazine-1, 4-dione, and butyric acid. Highlights: Optimized process for peanut meal Maillard Reaction products with the best sensory. Increased anti-oxidative activity of peanut meal Maillard Reaction products. Increased anti-oxidative (mainly phenolic) compounds after Maillard Reaction.